Just the facts, ma'am : a writer's guide to investigators and investigation techniques - Fallis, Greg (Howdunit series, 1998)
Whether your story involves snooping on a wayward husband or conducting corporate espionage, this guide will help you get the facts straight. You'll learn everything you need to know about all types of public and private investigators - such as background, skills and credentials. Drawing on 20 years of experience, author Greg Fallis then shows you how these professionals really operate.